ANALISIS FAKTOR LOYALITAS MAHASISWA TERHADAP UMKM BAKSO KUAH DI AREA KAMPUS - Nadia Taqiya Ihsan; Nasywa Laila Ramadhani; Nitha Amanda; Zainarti Zainarti (JURNAL ILMIAH EKONOMI DAN MANAJEMEN, 2026)
This study aims to analyze the factors influencing student loyalty toward meatball soup micro, small, and medium enterprises (MSMEs) in the campus area. This research employs a descriptive qualitative approach with data collection techniques including interviews, observations, and documentation to obtain a comprehensive understanding of student consumer behavior and business practices implemented by meatball soup MSME owners. The results indicate that student loyalty is influenced by several key factors, namely the quality of taste and broth, affordable pricing, strategic business location, and the quality of service that is friendly and responsive. In addition, emotional closeness between sellers and consumers plays an important role in creating comfort and encouraging repeat purchases. Overall, consistent product quality, good service, and positive interpersonal relationships are proven to jointly contribute to increasing student loyalty toward meatball soup MSMEs in the campus environment. This study is expected to serve as an evaluation material and reference for campus culinary MSME actors in improving competitiveness and business sustainability.